2019
DOI: 10.1177/1059601118820966
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Taxonomy of Workplace Bullying Intervention Types: Informing Research Directions and Supporting Organizational Decision Making

Abstract: Recently much has been done to increase our understanding of workplace bullying including its causes, consequences, and prevalence. Although identification of possible interventions has advanced the field, systematic evidence on the efficacy and effectiveness of specific interventions is lacking. At the same time, organizations are under increasing pressure to prevent and manage workplace bullying more effectively. The aim of this study is to develop and refine a taxonomy of workplace bullying intervention typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…The above intervention examples were included in a recently developed typology [ 66 ]. Caponecchia et al identified 11 core intervention types (investigation, codes of conduct, policy; EAP and counselling, bullying awareness training, coaching, system-wide intervention, skills training and development, values statements, local resolution, and organizational redesign).…”
Section: Discussionmentioning
confidence: 99%
“…The above intervention examples were included in a recently developed typology [ 66 ]. Caponecchia et al identified 11 core intervention types (investigation, codes of conduct, policy; EAP and counselling, bullying awareness training, coaching, system-wide intervention, skills training and development, values statements, local resolution, and organizational redesign).…”
Section: Discussionmentioning
confidence: 99%
“…Our model also implies the possibility of specific leadership development interventions aimed at reducing workplace bullying. Recently, Caponecchia et al ( 2020 ) developed and presented a taxonomy of workplace bullying intervention types. They mentioned leadership as one possible factor relating to bullying that could be targeted by organizational interventions (Caponecchia et al, 2020 , p. 106) but did not provide specific details.…”
Section: Managerial Implications and Future Researchmentioning
confidence: 99%
“…Recently, Caponecchia et al ( 2020 ) developed and presented a taxonomy of workplace bullying intervention types. They mentioned leadership as one possible factor relating to bullying that could be targeted by organizational interventions (Caponecchia et al, 2020 , p. 106) but did not provide specific details. In contrast, our model suggests that leadership development interventions designed to reduce workplace bullying could focus on encouraging more empowering and communal leadership behaviors, while explaining the tradeoff between the benefits and costs of using more autocratic and agentic approaches.…”
Section: Managerial Implications and Future Researchmentioning
confidence: 99%
“…It impacts the morale of employees and influences workers' productivity [47,48]. Thus, enterprises and human resource departments should not only promote ways of reducing incivility but also raise employee awareness of which actions comprise covert or overt incivility by using problem-focused coping strategies [49] to implement civility training programs in the workplace [50,51]. In this way, incivility might be identified and rejected regardless of the type of incivility or the leader's gender.…”
Section: Practical Implicationsmentioning
confidence: 99%